Multibiomass and Natural Marine Waste Catalyst Copyrolysis: Exploring Synergy, Isoconversional Kinetics, Thermodynamics, and Mechanism - Sabah Mariyam (14150859) (2023)
This study presents the copyrolysis of three biomasses (date pits, cow manure, and coffee waste) and explores the potential of utilizing natural waste catalysts—seashell (SS) and cuttlebone (CB)—to improve the kinetics and thermodynamics of the process. Mixing the feeds led to positive synergistic effects, particularly at a heating rate of 10 K/min or higher. By employing three model-free kinetic methods, the estimated activation energy (Ea) was lower for the ternary feed than the single feeds, and 20 wt.% of the feed with SS and CB catalysts was added. The Ea reduced from 162 kJ/mol for the ternary feed by 25.6% (~121 kJ/mol) and 21.6% (154 kJ/mol) in the presence of SS and CB, respectively. The thermodynamic parameters were positive for all the noncatalytic feeds, resulting in endothermic, nonspontaneous reactions and increased disorder or randomness. Catalysts influenced the thermodynamic parameters, making the process more energy efficient. The results are the utilization of cheap, eco-friendly feeds and catalysts for sustainable energy production using copyrolysis. Other Information Published in: International Journal of Energy Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2023/2140032